Chlorine-resistant and acid-resistant composite nanofiltration membrane and preparation method thereof

By using an interface polymerization method containing polyols or phenol compounds and tripyrochlorine in the nanofiltration membrane, combined with acid binding agents with alkaline compounds, the existing nanofiltration membrane's performance degradation in acidic and high-chlorine environments is solved, and high-efficiency nanofiltration separation performance is achieved with chlorine resistance and acid resistance.

CN119746648AInactive Publication Date: 2025-04-04BEIJING UNIV OF TECH

Patent Information

Application Number
CN202411976172.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing nanofiltration membranes are prone to hydrolysis of amide bonds when treating acidic wastewater, resulting in changes in membrane structure and degradation of separation performance, and poor chlorine resistance, which affects the stability of long-term operation.

Method used

Polyols or phenol compounds containing no less than 2 hydroxyl groups are used for interfacial polymerization with cyanochloride to form a loose network structure, combining alkaline compounds as acid binding agents, neutralizing the by-product hydrochloric acid, and promoting interfacial polymerization reaction.

Benefits of technology

The composite nanofiltration membrane has achieved good chlorine and acid resistance stability, maintained efficient nanofiltration separation performance, and the preparation process is simple and suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005220497570000011
    Figure HDA0005220497570000011
  • Figure HDA0005220497570000012
    Figure HDA0005220497570000012
  • Figure HDA0005220497570000021
    Figure HDA0005220497570000021
Patent Text Reader

Abstract

The invention discloses a chlorine-resistant and acid-resistant composite nanofiltration membrane and a preparation method thereof, and belongs to the technical field of membrane separation. A polyhydric alcohol or / phenol compound monomer containing no less than two hydroxyl groups is subjected to interfacial polymerization with cyanuric chloride, so that a relatively loose network structure can be formed, and selective separation of dye and salt is realized. As a hydrochloric acid (HCl) byproduct can be generated in the reaction process, an alkaline compound is added as an acid-binding agent to neutralize HCl and promote the interfacial polymerization reaction, the formed composite nanofiltration membrane structure does not contain amino groups and polyamide bonds sensitive to active chlorine, the reaction sites of the active chlorine are reduced, and the chlorine-resistant stability of the membrane is good. Meanwhile, the polymer film contains a triazine ring structure, and a formed ether bond has good chemical stability, so that the acid-resistant stability of the film is good. The prepared composite nanofiltration membrane has good nanofiltration separation performance, shows good chlorine-resistant and acid-resistant stability, and can be used for separation of dyes / salts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a composite nanofiltration membrane and a preparation method thereof, in particular to a chlorine-resistant and acid-resistant composite nanofiltration membrane, a preparation method and application thereof, and belongs to the technical field of membrane separation. Technical Background

[0002] With the rapid advancement of urbanization and industrialization, water consumption and wastewater discharge have increased, water shortage and water pollution have intensified. Industrial wastewater reuse can achieve product resource recovery, clean energy, and meet the goal of sustainable development. Industrial wastewater treatment technologies mainly include adsorption, electrochemical, ion exchange, chemical precipitation, membrane separation, etc. Membrane separation technology is widely used because of its green and low energy consumption. Among them, nanofiltration membrane can achieve efficient separation of multivalent salts and small molecular organic matter, and has been widely used in wastewater treatment, seawater desalination and pharmaceutical fields.

[0003] At present, commercial nanofiltration membranes are mainly polyamide nanofiltration membranes prepared by interfacial polymerization. When treating acidic wastewater, the amide bond is easily hydrolyzed, resulting in changes in the membrane structure and a decrease in its separation performance. In addition, in actual application, sodium hypochlorite is required to clean the membrane to reduce membrane contamination caused during operation, and the commercial polyamide membrane has poor chlorine resistance, which will cause the membrane separation performance to decay. The preparation of chlorine-resistant membranes mainly includes protecting the polyamide layer or developing new chlorine-resistant structures. Patent CN114504956A uses compounds containing active functional groups to graft polyamide membranes, caps the amino groups remaining on the membrane surface, and soaks in a 2mg / L sodium hypochlorite solution for 8h. The retention rate of the membrane decreases by about 5%. However, the membrane surface grafting method is complicated to operate, and the surface is prone to uneven grafting, resulting in defects. Patent CN 113797762A blends hydrolyzed carboxyl-terminated styrene maleic anhydride with polymer membrane materials into a homogeneous casting solution, uses a phase inversion method to prepare a base membrane material, and then obtains a chlorine-resistant polyester nanofiltration membrane through an esterification reaction between tannic acid and carboxyl groups. After soaking in a 2g / L sodium hypochlorite solution for 1 hour, the surface morphology does not change much. Patent CN 117753221A introduces graphene quantum dots on the surface of the base membrane, and then uses a mixed solution containing mannitol, alkaline compounds and piperazine as the aqueous phase to perform interfacial polymerization with the acyl chloride organic phase to obtain a polyester and polyamide layer. The pure water flux of the membrane is 23Lm -2 h -1 bar -1 The retention rate of sodium sulfate is 98.35%; after being soaked in 300ppm sodium hypochlorite solution for 72 hours, the pure water flux of the membrane is 23.75Lm -2 h -1 bar -1 , and the rejection rate of sodium sulfate is 98.02%. Although the chlorine resistance of these nanofiltration membranes has improved, their acid resistance is still greatly challenged.

[0004] The amide bonds in conventional polyamide (PA) composite nanofiltration membranes are easily damaged by H in an acidic environment. + Attack, hydrolysis occurs, resulting in damage to the membrane structure and reduced separation performance. Research on acid-resistant membranes is mostly focused on polymer membranes such as triazine polyamines, polysulfonamides, and polyureas. Among them, triazine polyamines are mainly obtained by interfacial polymerization with cyanuric chloride (CC) instead of traditional trimesoyl chloride (TMC) and polyamine monomers. Since the carbon-nitrogen bond in the triazine polyamine replaces the easily hydrolyzed amide bond in PA, it has good chemical stability and can improve the acid resistance of the nanofiltration membrane. Patent CN 117839448A uses melamine as the aqueous phase monomer and cyanuric chloride as the organic phase monomer, and interfacial polymerization is used to obtain a composite nanofiltration membrane. The water flux of the composite membrane is 18.27Lm -2 h -1 The interception rate of magnesium sulfate is 98.6%. After soaking in 20% hydrochloric acid solution for one week, the interception rate of magnesium sulfate is 97.7%, and the flux is 20.60Lm -2 h -1 . In order to solve the problem of the gradual decrease in the activity of cyanuric chloride substitution reaction, patent CN 107930412A discloses a polyamide-triazineamine nanofiltration composite membrane. The invention uses cyanuric chloride and polyamine as raw materials, and prepares a polytriazineamine precursor through a nucleophilic substitution reaction. The polytriazineamine precursor is used as an aqueous phase monomer to carry out interfacial polymerization with polyacyl chloride oil phase monomers to prepare an acid-resistant polyamide-triazineamine nanofiltration composite membrane. Patent CN 116585914A hydrophilically modifies cyanuric chloride to graft functional groups containing amino groups and other hydrophilic groups, and uses the hydrophilically modified substance as an aqueous phase monomer to carry out interfacial polymerization with acyl chlorides to obtain a composite nanofiltration membrane with a retention rate of 99.3% for magnesium sulfate and a flux of 2.94Lm -2 h -1 bar -1 After the membrane was immersed in a 20wt% sulfuric acid solution at 70°C for 30 days, the rejection rate was still maintained above 96%. However, these methods are complicated to operate, and the presence of a large number of amine groups affects the membrane's tolerance to hypochlorous acid cleaning solutions. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a chlorine-resistant and acid-resistant composite nanofiltration membrane and a preparation method thereof.

[0006] A chlorine-resistant and acid-resistant composite nanofiltration membrane and a preparation method thereof, mainly comprising:

[0007] (1) Preparation of aqueous monomer solution

[0008] Add the weighed polyol monomer into deionized water and stir thoroughly to obtain an aqueous phase solution with a mass concentration of 0.2 to 16.0%, add an alkaline compound solution as an acid binding agent, and adjust the pH value of the solution to 8 to 12;

[0009] (2) Preparation of oil phase monomer solution

[0010] Add cyanuric chloride into an organic solvent and stir thoroughly to obtain an oil phase solution with a mass concentration of 0.05 to 15.0%;

[0011] (3) Preparation of composite nanofiltration membrane by interfacial polymerization

[0012] The cut ultrafiltration membrane is placed in deionized water, shaken and cleaned thoroughly, then immersed in the aqueous solution prepared in step (1), taken out after 1-30 minutes, and the remaining droplets on the surface are removed, and then immersed in the oil solution prepared in step (2), after interfacial polymerization reaction for 0.5-50 minutes, taken out, placed in an oven, and heat treated at 30-95°C for 5-95 minutes to obtain a polyether composite nanofiltration membrane.

[0013] Furthermore, the polyol monomer is a polyol or / phenol compound having no less than 2 hydroxyl groups, including but not limited to phloroglucinol, resveratrol, and ethylenediaminetetraethanol.

[0014] Furthermore, the alkaline compound includes but is not limited to N,N-diisopropylethylamine, triethylamine, potassium hydroxide, sodium carbonate, sodium hydroxide, preferably triethylamine and sodium hydroxide.

[0015] Furthermore, the organic solvent used to prepare the oil phase solution includes but is not limited to n-hexane, n-heptane, cyclohexane, N,N-dimethylpyrrolidone, and the like.

[0016] Furthermore, the ultrafiltration base membrane is a polysulfone, polyethersulfone, polyvinylidene fluoride, or polyetheretherketone ultrafiltration membrane with a molecular weight cutoff of 10-500 kDa, preferably 50-70 kDa.

[0017] The membrane obtained by the present invention is used for filtering dyes and further for dye / salt separation. Furthermore, in the dye / salt separation, the salt is selected from one or more of Na2SO4, MgSO4, NaCl, and MgCl2, and the dye is selected from one or more of methyl orange, chrome blue black R, Congo red, and Evans blue.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] The present invention adopts polyol or / phenol compound monomer containing not less than 2 hydroxyl groups and cyanuric chloride interfacial polymerization to form a loose network structure, thereby realizing selective separation of dye and salt. Since hydrochloric acid (HCl) byproduct is generated during the reaction, an alkaline compound is added as an acid binding agent to neutralize HCl, which can promote the interfacial polymerization reaction. The formed composite nanofiltration membrane structure does not contain amino groups and polyamide bonds sensitive to active chlorine, reduces the reactive sites of active chlorine, and makes the membrane have good chlorine resistance stability. At the same time, because the polymer membrane contains a triazine ring structure, the formed ether bond has good chemical stability, thereby making the membrane have good acid resistance stability. The prepared composite nanofiltration membrane has good nanofiltration separation performance and shows good chlorine and acid resistance stability. For example, the composite membrane prepared in Example 3 has a retention rate of 98.35% for chrome blue black R, a water flux of 22LMH / bar, and a retention rate of 97.90% for chrome blue black R after soaking in 15wt% hydrochloric acid for 30 days, and a retention rate of 93.85% after soaking for 60 days; after soaking in 15wt% sodium sulfate for 30 days, the retention rate of chrome blue black R is 97.82%, and the retention rate of 94.88% after soaking for 60 days, showing good acid resistance stability. Secondly, because the composite membrane does not contain amine groups and polyamide groups susceptible to active chlorine attack, after soaking in 1000ppm sodium hypochlorite for 30 days, the retention rate of chrome blue black R is 98.78%, and the retention rate of 96.26% after soaking for 60 days, showing good chlorine resistance stability. The present invention adopts interfacial polymerization method to prepare the membrane, the preparation process is simple and convenient, and is suitable for application in the field of dye wastewater treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The schematic diagram of the operation process of preparing the composite nanofiltration membrane in Example 3 of the present invention and the interfacial polymerization reaction formula of phloroglucinol and cyanuric chloride are shown;

[0021] Figure 2 Scanning electron microscope images of the surface of the composite nanofiltration membrane prepared by using different alkaline compound acid-binding agents of the present invention, wherein the acid-binding agent in Figure (a) is N,N-diisopropylethylamine, the acid-binding agent in Figure (b) is triethylamine, and the acid-binding agent in Figure (c) is sodium hydroxide;

[0022] Figure 3 The separation performance of the composite nanofiltration membrane prepared in Example 3 of the present invention for different salts and dyes;

[0023] Figure 4 The chlorine resistance stability of the composite nanofiltration membrane prepared in Example 3 of the present invention, specifically, the separation performance change for 100 ppm chrome blue black R after being treated with 1000 ppm sodium hypochlorite for 60 days.

[0024] Figure 5The acid stability of the composite nanofiltration membrane prepared in Example 3 of the present invention is as follows: (a) the separation performance of the membrane for 100 ppm chrome blue black R after being immersed in 15 wt % sulfuric acid for 60 days, and (b) the separation performance of the membrane for 100 ppm chrome blue black R after being treated with 15 wt % hydrochloric acid. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] The present invention is further described in detail below in conjunction with the accompanying drawings:

[0027] Example 1

[0028] First, resveratrol was added to deionized water and stirred thoroughly to obtain an aqueous solution with a mass concentration of 0.2%, and sodium hydroxide solution was added dropwise to adjust the pH value of the aqueous solution to 8. Second, cyanuric chloride was added to n-heptane and stirred thoroughly to obtain an oil solution with a mass concentration of 0.05%.

[0029] The cut polysulfone ultrafiltration membrane was placed in deionized water, and after shaking and washing, the remaining water droplets were removed, and the membrane was immersed in an aqueous solution, taken out after 30 minutes, and the remaining droplets on the surface were removed. The membrane was then immersed in an oil phase solution, and taken out after 50 minutes. The composite membrane was placed in an oven for heat treatment at 30°C for 95 minutes to obtain a resveratrol / trichloroethylene polyether composite nanofiltration membrane.

[0030] The prepared resveratrol / melamine polyether composite nanofiltration membrane was tested for nanofiltration separation performance in a cross-flow nanofiltration device. The test operating conditions were: room temperature, 100 ppm chrome blue black R solution as the feed liquid, and a pressure of 0.2 MPa. The test results showed that the prepared composite nanofiltration membrane had a retention rate of 76.81% for chrome blue black R and a flux of 110 Lm -2 h -1 bar -1 .

[0031] Example 2

[0032] First, ethylenediaminetetraethanol was added to deionized water and stirred thoroughly to obtain an aqueous phase solution with a mass concentration of 16.0%, and sodium hydroxide solution was added dropwise to adjust the pH value of the aqueous phase solution to 12. Second, cyanuric chloride was added to n-hexane and stirred thoroughly to obtain an oil phase solution with a mass concentration of 15.0%.

[0033] The cut polyethersulfone membrane was placed in deionized water for shaking cleaning, and the remaining droplets were removed. The membrane was immersed in an aqueous solution and taken out after 1 minute. The remaining droplets on the surface were removed, and the membrane was immersed in an oil solution and taken out after 0.5 minutes. The composite membrane was placed in an oven for heat treatment at 95°C for 5 minutes to obtain an ethylenediaminetetraethanol / tricyanuric chloride polyether composite nanofiltration membrane.

[0034] The prepared ethylenediaminetetraethanol / trichloroethylene composite nanofiltration membrane was tested for nanofiltration separation performance in a cross-flow nanofiltration device. The test operating conditions were: room temperature, 100ppm chrome blue black R solution as feed liquid, and 0.2MPa as pressure. The test results showed that the retention rate of the prepared composite nanofiltration membrane for chrome blue black R was 90.06%, and the flux was 88.57Lm -2 h -1 bar -1 .

[0035] Example 3

[0036] First, phloroglucinol was added to deionized water and stirred thoroughly to obtain an aqueous phase solution with a mass concentration of 0.8%, and sodium hydroxide solution was added dropwise to adjust the pH value of the aqueous phase solution to 10. Secondly, cyanuric chloride was added to n-hexane and stirred thoroughly to obtain an oil phase solution with a mass concentration of 0.7%.

[0037] The cut polyetheretherketone ultrafiltration membrane was placed in deionized water for shaking cleaning, and the remaining droplets were removed. The membrane was immersed in an aqueous solution and taken out after 5 minutes. The remaining droplets on the surface were removed, and the membrane was immersed in an oil solution and taken out after 15 minutes. The composite membrane was placed in an oven for heat treatment at 75°C for 8 minutes to obtain a pyroglobulin / melamine polyether composite nanofiltration membrane.

[0038] The prepared phloroglucinol / melamine polyether composite nanofiltration membrane was tested for nanofiltration separation performance in a cross-flow nanofiltration device. The test operating conditions were: room temperature, 100 ppm chrome blue black R solution as feed liquid, and 0.2 MPa as pressure. The test results showed that the prepared composite nanofiltration membrane had a retention rate of 96.84% for chrome blue black R and a flux of 22 Lm -2 h -1 bar -1 .

[0039] Example 4

[0040] First, resveratrol was added to deionized water and stirred thoroughly to obtain a 1.2% aqueous solution, and sodium carbonate solution was added dropwise to adjust the pH value of the aqueous solution to 11. Second, cyanuric chloride was added to n-heptane and stirred thoroughly to obtain an oil solution with a mass concentration of 0.9%.

[0041] After the polysulfone ultrafiltration membrane was placed in deionized water for shaking cleaning, the remaining water droplets were removed, the membrane was immersed in an aqueous solution for 5 minutes and then taken out, the remaining droplets on the surface were removed, the membrane was immersed in an oil phase solution for 10 minutes and then taken out, and the composite membrane was placed in an oven for heat treatment at 65°C for 10 minutes to obtain a resveratrol / trichloroethylene polyether composite nanofiltration membrane.

[0042] The prepared resveratrol / melamine polyether composite nanofiltration membrane was tested for nanofiltration separation performance in a cross-flow nanofiltration device. The test operating conditions were: room temperature, 100 ppm chrome blue black R solution as feed liquid, and 0.2 MPa as pressure. The test results showed that the prepared composite nanofiltration membrane had a retention rate of 90.68% for chrome blue black R and a flux of 42.76 Lm -2 h -1 bar -1 .

[0043] Example 5

[0044] First, phloroglucinol was added to deionized water and stirred thoroughly to obtain an aqueous solution with a mass concentration of 10.0%, and sodium hydroxide was added to adjust the pH value of the aqueous solution to 9. Second, cyanuric chloride was added to n-heptane and stirred thoroughly to obtain an oil solution with a mass concentration of 9.0%.

[0045] The cut polysulfone ultrafiltration membrane was placed in deionized water for shaking cleaning and then fixed on a glass plate to remove remaining water droplets. The membrane was immersed in an aqueous solution for 12 minutes and then taken out. After removing the remaining water droplets on the surface, the membrane was immersed in an oil phase solution for 15 minutes and then taken out. Finally, the composite membrane was placed in an oven for heat treatment at 60°C for 25 minutes to obtain a pyroglucin / melamine polyether composite nanofiltration membrane.

[0046] The prepared phloroglucinol / trichlorocyanuric acid polyether composite nanofiltration membrane was tested for nanofiltration separation performance in a cross-flow nanofiltration device. The test operating conditions were: room temperature, the feed liquid was 100ppm chrome blue black R solution, and the pressure was 0.2MPa. The test results showed that the prepared composite nanofiltration membrane had a retention rate of 97.44% for chrome blue black R and a flux of 10.04Lm -2 h -1 bar -1 .

[0047] Example 6

[0048] First, ethylenediaminetetraethanol was added to deionized water and stirred thoroughly to obtain a water phase solution with a mass concentration of 0.6%, and N,N-diisopropylethylamine solution was added dropwise to adjust the pH value of the water phase solution to 12. Secondly, cyanuric chloride was added to N,N-dimethylpyrrolidone and stirred thoroughly to obtain an oil phase solution with a mass concentration of 0.5%.

[0049] The cut polyvinylidene fluoride ultrafiltration membrane was placed in deionized water for shaking cleaning, and the remaining droplets were removed. The membrane was immersed in an aqueous solution for 8 minutes and then taken out. After removing the remaining droplets on the surface, the membrane was immersed in an oil solution and taken out after 9 minutes. The composite membrane was placed in an oven for heat treatment at 80°C for 8 minutes to obtain an ethylenediaminetetraethanol / trichloroethylene polyether composite nanofiltration membrane.

[0050] The prepared EDTA / melamine polyether composite nanofiltration membrane was tested for nanofiltration separation performance in a cross-flow nanofiltration device. The test operating conditions were: room temperature, 100 ppm chrome blue black R solution as feed liquid, and 0.2 MPa as pressure. The test results showed that the prepared composite nanofiltration membrane had a retention rate of 73.56% for chrome blue black R and a flux of 120 Lm -2 h -1 bar -1 .

[0051] Example 7

[0052] First, resveratrol was added to deionized water and stirred thoroughly to obtain an aqueous solution with a mass concentration of 5.0%, and triethylamine was added dropwise to adjust the pH value of the aqueous solution to 11. Second, cyanuric chloride was added to n-heptane and stirred thoroughly to obtain an oil solution with a mass concentration of 4.5%.

[0053] The cut polyetheretherketone ultrafiltration membrane was placed in deionized water for shaking cleaning, and the remaining droplets were removed. The membrane was immersed in an aqueous solution for 6.5 minutes, taken out, and the remaining droplets on the surface were removed. The membrane was immersed in an oil phase solution and taken out after 4.5 minutes. The composite membrane was placed in an oven for heat treatment at 70°C for 7.5 minutes to obtain a resveratrol / trichloroethylene polyether composite nanofiltration membrane.

[0054] The prepared resveratrol / melamine polyether composite nanofiltration membrane was tested for nanofiltration separation performance in a cross-flow nanofiltration device. The test operating conditions were: room temperature, 100 ppm chrome blue black R solution as feed liquid, and 0.2 MPa as pressure. The test results showed that the prepared composite nanofiltration membrane had a retention rate of 52.71% for chrome blue black R and a flux of 154.29 Lm -2 h -1 bar -1 .

[0055] Example 8

[0056] First, phloroglucinol was added to deionized water and stirred thoroughly to obtain an aqueous phase solution with a mass concentration of 0.9%, and sodium hydroxide solution was added dropwise to adjust the pH value of the aqueous phase solution to 10.0. Second, cyanuric chloride was added to N, N-dimethylpyrrolidone and stirred thoroughly to obtain an oil phase solution with a mass concentration of 0.75%.

[0057] After the polyetheretherketone ultrafiltration membrane was placed in deionized water for shaking cleaning, the remaining droplets were removed, and the membrane was immersed in an aqueous solution and taken out after 6.5 minutes. After removing the remaining droplets on the surface, the membrane was immersed in an oil solution and taken out after 4.5 minutes. The composite membrane was placed in an oven for heat treatment at 50°C for 35 minutes to obtain a pyroglobulin / melamine polyether composite nanofiltration membrane.

[0058] The prepared phloroglucinol / melamine polyether composite nanofiltration membrane was tested for nanofiltration separation performance in a cross-flow nanofiltration device. The test operating conditions were: the feed liquid was 100ppm chrome blue black R solution, the test was conducted at room temperature, and the pressure was 0.2MPa. The test results showed that the prepared composite nanofiltration membrane had a retention rate of 76.56% for chrome blue black R and a flux of 85.72Lm -2 h -1 bar -1 .

[0059] Example 9

[0060] First, phloroglucinol was added to deionized water and stirred thoroughly to obtain an aqueous phase solution with a mass concentration of 6.5%, and potassium hydroxide solution was added dropwise to adjust the pH value of the aqueous phase solution to 12. Secondly, cyanuric chloride was added to N, N-dimethylpyrrolidone and stirred thoroughly to obtain an oil phase solution with a mass concentration of 7.5%.

[0061] After the polyetheretherketone ultrafiltration membrane was placed in deionized water for shaking cleaning, the remaining droplets were removed, and the membrane was immersed in an aqueous solution and taken out after 6.5 minutes. After removing the remaining droplets on the surface, the membrane was immersed in an oil solution and taken out after 4.5 minutes. The composite membrane was placed in an oven for heat treatment at 85°C for 6 minutes to obtain a pyroglobulin / melamine polyether composite nanofiltration membrane.

[0062] The prepared phloroglucinol / melamine polyether composite nanofiltration membrane was tested for nanofiltration separation performance in a cross-flow nanofiltration device. The test operating conditions were: room temperature, 100 ppm chrome blue black R solution as feed liquid, and 0.2 MPa as pressure. The test results showed that the prepared composite nanofiltration membrane had a retention rate of 98.05% for chrome blue black R and a flux of 6.93 Lm -2 h -1 bar -1 .

[0063] The surfaces of the composite nanofiltration membranes prepared in Examples 3, 6, and 7 were observed using a scanning electron microscope. Figure 1 As shown. It can be seen that the surface structure uniformity of the nanofiltration membrane prepared by using N,N-diisopropylethylamine as the acid-binding agent is poor; the surface structure of the nanofiltration membrane prepared by using triethylamine as the acid-binding agent has obvious micropores and a discontinuous separation layer; the surface structure of the nanofiltration membrane prepared by using sodium hydroxide as the acid-binding agent is uniform, the separation layer is continuous, and the membrane surface morphology is good.

[0064] The composite nanofiltration membrane prepared in Example 3 has a retention rate of 73.76%, 14.64%, 12.82%, and 4.01% for 1.0 g / L of Na2SO4, MgSO4, NaCl, and MgCl2, respectively, and a retention rate of 17.98%, 96.84%, 99.13%, and 99.80% for 100 ppm of methyl orange, chrome blue black R, Congo red, and Evans blue, respectively. The low retention rate for sodium and / or magnesium indicates that the nanofiltration membrane has a good dye / salt separation performance.

[0065] The composite nanofiltration membrane prepared in Example 3 was immersed in a 1000 ppm sodium hypochlorite solution for 60 days to test its chlorine resistance stability. The test results are shown in the attached figure. Figure 4 As shown in the figure, it can be seen that the flux and rejection rate of the nanofiltration membrane remain stable. When the immersion time reaches 60 days, the rejection rate remains at 96.26%. This indicates that the nanofiltration membrane without amine groups and amide bonds susceptible to active chlorine attack in the separation layer structure has chlorine resistance.

[0066] The composite nanofiltration membrane prepared in Example 3 was immersed in a 15wt% sulfuric acid solution for 60 days, and the membrane prepared in Example 3 was immersed in a 15wt% hydrochloric acid solution for 60 days to test its acid resistance stability. The test results are shown in the attached Figure 5 As shown. It can be seen that the flux of the nanofiltration membrane increased slightly, and the retention rate remained basically stable. After 60 days in 15wt% sulfuric acid solution, the retention rate was 94.88% (see Figure 2). Figure 5 After 60 days in 15wt% hydrochloric acid solution, the retention rate was 93.85% (see Figure 5). Figure 5 b). This indicates that the composite nanofiltration membrane prepared by the present invention has good acid resistance and stability.

Claims

1. A chlorine-resistant and acid-resistant composite nanofiltration membrane and a preparation method thereof, characterized in that: The main steps include: (1) Preparation of aqueous monomer solution Add the weighed polyol monomer into deionized water and stir thoroughly to obtain an aqueous phase solution with a mass concentration of 0.2 to 16.0%, add an alkaline compound solution as an acid binding agent, and adjust the pH value of the solution to 8 to 12; (2) Preparation of oil phase monomer solution Add cyanuric chloride into an organic solvent and stir thoroughly to obtain an oil phase solution with a mass concentration of 0.05 to 15.0%; (3) Preparation of composite nanofiltration membrane by interfacial polymerization The cut ultrafiltration membrane is placed in deionized water, shaken and cleaned thoroughly, then immersed in the aqueous solution prepared in step (1), taken out after 1-30 minutes, and the remaining droplets on the surface are removed, and then immersed in the oil solution prepared in step (2), after interfacial polymerization reaction for 0.5-50 minutes, taken out, placed in an oven, and heat treated at 30-95°C for 5-95 minutes to obtain a polyether composite nanofiltration membrane.

2. The method according to claim 1, characterized in that The polyol monomer is a polyol or / phenol compound having no less than 2 hydroxyl groups, including but not limited to phloroglucinol, resveratrol, and ethylenediaminetetraethanol.

3. The method according to claim 1, characterized in that The alkaline compound includes but is not limited to N,N-diisopropylethylamine, triethylamine, potassium hydroxide, sodium carbonate, sodium hydroxide, preferably triethylamine and sodium hydroxide.

4. The method according to claim 1, characterized in that The organic solvent used to prepare the oil phase solution includes, but is not limited to, n-hexane, n-heptane, cyclohexane, N,N-dimethylpyrrolidone, and the like.

5. The method according to claim 1, characterized in that The ultrafiltration base membrane is a polysulfone, polyethersulfone, polyvinylidene fluoride, polyetheretherketone ultrafiltration membrane with a molecular weight cutoff of 10-500kDa, preferably 50-70kDa.

6. A composite nanofiltration membrane prepared according to the method according to any one of claims 1 to 5.

7. Use of the composite nanofiltration membrane prepared by the method according to any one of claims 1 to 5 for filtering dyes.

8. Use according to claim 7 for separation of dyes / salts.

9. The use according to claim 8, wherein in the dye / salt separation, the salt is selected from one or more of Na2SO4, MgSO4, NaCl, and MgCl2, and the dye is selected from one or more of methyl orange, chrome blue black R, Congo red, and Evans blue.

10. The use according to claim 7 or 8, wherein the solution is acidic and / or contains sodium hypochlorite.

Citation Information

Patent Citations

  • Preparation method of acid-resistant poly(amide-triazine-amine) nanofiltration composite membrane

    CN107930412A

  • Preparation method of chlorine-resistant polyester nanofiltration membrane

    CN113797762A

  • Chlorine-resistant nanofiltration membrane and preparation method thereof

    CN114504956A

  • Preparation method of acid-resistant nanofiltration membrane

    CN116585914A

  • Nanofiltration membrane with chlorine resistance and water flux and preparation method thereof

    CN117753221A

Cited By

  • Polyamide nanofiltration membrane based on resveratrol middle layer as well as preparation method and application of polyamide nanofiltration membrane

    CN120393756A

  • A polyamide nanofiltration membrane based on a resveratrol intermediate layer, and its preparation method and application

    CN120393756B

  • Nanofiltration membrane and preparation method thereof

    CN121623599A